2017
DOI: 10.1002/mnfr.201700230
|View full text |Cite
|
Sign up to set email alerts
|

l‐Ornithine and l‐lysine stimulate gastrointestinal motility via transient receptor potential vanilloid 1

Abstract: Orally administered Orn and Lys stimulate GI motility via TRPV1, mAChR and NO synthase in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…l -Pipecolic acid can promote intestinal propulsive rate by increasing the levels of 5-hydroxytryptamine and acetylcholine in the colon , NCC could improve the contents of DCA, UDCA, CDCA, acetic acid, butyric acid, l -pipecolic acid, l -ornithine, and l -lysine through improving the relative abundance of Lactobacillus , Prevotellaceae_UCG-001 , and Anaerotruncus . Finally, NCC improved intestinal motility, and constipation was cured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…l -Pipecolic acid can promote intestinal propulsive rate by increasing the levels of 5-hydroxytryptamine and acetylcholine in the colon , NCC could improve the contents of DCA, UDCA, CDCA, acetic acid, butyric acid, l -pipecolic acid, l -ornithine, and l -lysine through improving the relative abundance of Lactobacillus , Prevotellaceae_UCG-001 , and Anaerotruncus . Finally, NCC improved intestinal motility, and constipation was cured.…”
Section: Resultsmentioning
confidence: 99%
“…80 L-Ornithine and L-lysine can enhance intestinal motility by stimulating intestinal secretion through transient receptor potential vanilloid 1, muscarinic acetylcholine receptor, and NO synthase. 90,91 NCC could improve the contents of DCA, UDCA, CDCA, acetic acid, butyric acid, L-pipecolic acid, L-ornithine, and L-lysine through improving the relative abundance of Lactobacillus, Prevotella-ceae_UCG-001, and Anaerotruncus. Finally, NCC improved intestinal motility, and constipation was cured.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, PIPA has rarely been studied as a gut metabolite, and its relationship to the host has been rarely studied as well. A recent study reported that orally taking L -lysine, which is a precursor of PIPA, could improve the small intestine propulsive rate in mice (Nakato et al, 2017). Although it seems that PIPA may be involved in intestinal motility, there is not an abundance of data or direct evidence to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate can be converted into N -acetylglutamate through catalysis, which then participates in arginine synthesis as a prerequisite for N -acetylornithine [ 30 ]. A study found that L -ornithine stimulated, but conversely, arginine suppressed, gastrointestinal motility after oral administration in mice [ 31 ]. Another cross-sectional study showed that levels of serum metabolites of N -acetyl- L -glutamic acid were significantly lower in constipated women of reproductive age than in healthy controls [ 32 ].…”
Section: Discussionmentioning
confidence: 99%